2022
DOI: 10.1371/journal.pgen.1010302
|View full text |Cite
|
Sign up to set email alerts
|

HAP40 is a conserved central regulator of Huntingtin and a potential modulator of Huntington’s disease pathogenesis

Abstract: Perturbation of huntingtin (HTT)’s physiological function is one postulated pathogenic factor in Huntington’s disease (HD). However, little is known how HTT is regulated in vivo. In a proteomic study, we isolated a novel ~40kDa protein as a strong binding partner of Drosophila HTT and demonstrated it was the functional ortholog of HAP40, an HTT associated protein shown recently to modulate HTT’s conformation but with unclear physiological and pathologic roles. We showed that in both flies and human cells, HAP4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 71 publications
2
8
0
Order By: Relevance
“…Mounting evidence suggests that HAP40 plays an important role in regulating HTT protein conformation and stability, as the addition of HAP40 is essential for forming a stable HTT complex that can be used to resolve HTT protein structure via cryo-electron microscopy [ 9 ]. Moreover, the expression of HAP40 alters the level of HTT in cultured cells [ 32 , 33 ]. Our current study also shows that the expression of HAP40 and HTT is positively correlated in different brain regions of mice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mounting evidence suggests that HAP40 plays an important role in regulating HTT protein conformation and stability, as the addition of HAP40 is essential for forming a stable HTT complex that can be used to resolve HTT protein structure via cryo-electron microscopy [ 9 ]. Moreover, the expression of HAP40 alters the level of HTT in cultured cells [ 32 , 33 ]. Our current study also shows that the expression of HAP40 and HTT is positively correlated in different brain regions of mice.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with the previous finding that the knockdown of HAP40 using shRNA promotes the aggregation of mHTT fragments in striatal cells [ 34 ]. However, one study reported that deletion of the Drosophila homolog of HAP40 (dHAP40) in a fly model expressing human full-length mHTT partially rescued degenerative phenotypes and prolonged lifespan [ 33 ]. It is noteworthy that although dHAP40 is a 40 kDa protein that interacts with dHtt, its binding affinity to human HTT is significantly reduced [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the interaction of the two proteins is likely essential for their function, as both proteins have co-evolved and their interaction is conserved in various species 15 . Interestingly, the protein levels and stability of both HAP40 and HTT are reduced in tissues from HD patients and mouse models 9 , 16 18 , suggesting that the reduction of their levels in cells may contribute to the pathophysiology of HD 8 , 18 . However, although the HTT-HAP40 complex is well characterised in vitro 10 , 12 , 15 , 18 , little is known regarding the extent of their interaction in vivo.…”
Section: Introductionmentioning
confidence: 99%